The Congress Role in the Formulation of National Program for Production and Use of Biodiesel (PNPB) - Pedro Araújo Pietrafesa; José Paulo Pietrafesa (Fronteiras: Journal of Social, Technological and Environmental Science, 2014)
This article aims to analyze the parliamentary participation in the formulation of the National Program for Production and Use of Biodiesel. The central argument is that congressmen are proactive and not just reactive to the presidency preferences, they also have skills and abilities to participate in decision-making process and propose alternatives to the design of public policies formulated within the Executive, and thus develop actions and make certain choices with regard to resources, time and attention devoted to the formulation of government public policy activities. The triangulation methodology will allow the observation more accurately of parliamentary involvement in the formulation of the new energy matrix of renewable fuels policy... Keywords: National Program for Production and Use of Biodiesel; formulation of public policies; Executive-Legislative relationship; parliamentary action; policy networks.